2010
DOI: 10.1017/s1041610210001754
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for staff education and training for older people with mental illness in long-term aged care

Abstract: Methodological weaknesses are common and highlight the need for further replication studies using strong research designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…A recent metaanalysis demonstrated that didactic training alone is unlikely to have any impact on professional practice in health-care settings [17]. Indeed, there is growing evidence to support the combination of didactic training and interactive workshops to induce changes in professional practice [18]. For example, LTC staff knowledge and attitudes on working with people with dementia were improved when an integrative approach to training was applied (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A recent metaanalysis demonstrated that didactic training alone is unlikely to have any impact on professional practice in health-care settings [17]. Indeed, there is growing evidence to support the combination of didactic training and interactive workshops to induce changes in professional practice [18]. For example, LTC staff knowledge and attitudes on working with people with dementia were improved when an integrative approach to training was applied (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on staff training focus on teaching skills to caring staff in reducing challenging behaviours in residents with dementia (Moyle, Hsu, Lieff, & Vernooij-Dassen, 2010). In line with person-centred care principles, these training programmes seek to encourage staff to interpret challenging behaviours from the point of view of persons with dementia (Edvardsson et al, 2008) and as an expression of an unmet need (Algase et al, 1996).…”
Section: Dementia Care Training and Educational Interventions In Clinmentioning
confidence: 99%
“…Difficulties in determining where the person ‘fits’ in a fragmented policy environment, and whether older people are ultimately worthy of service provision, are likely to make it easier for health professionals to shunt older people between services. Difficulties in navigating the system also lead to older people being housed in residential facilities where their mental health needs may not be adequately understood or addressed due to lack of training in how best to support mental health or manage patients with a mental illness (Moyle et al, 2010). …”
Section: Discussionmentioning
confidence: 99%